Penciptaan Kreasi Batik Kontemporer Bermuatan Lokal sebagai Upaya Pelestarian Batik Daerah Kabupaten Probolinggo - wulandari, sri; Ramadhan, Bayu Gilang; Prihantanto, Yudha (JPKS (Jurnal Pendidikan dan Kajian Seni), 2024)
Indonesia has a variety of extraordinary cultural products. One of them is batik art. A piece of batik not only displays aesthetic motifs but also has philosophical meanings inherent in the lives of the surrounding community. Each region has various motifs that convey the local nuances of that area. Genggong flowers are a typical flower that grows abundantly in Karangbong Village, Pajarakan District, Probolinggo Regency. The existence of the Genggong flower, which is now extinct, has been immortalized as the name of an Islamic boarding school, namely the Zainul Hasan Genggong Islamic Boarding School. Through research with local community figures, the Genggong flower has a history for the people who live around the Islamic boarding school. This became a source of inspiration for the creation of batik creations with a Genggong flower motif, combined with the potential of the surrounding nature. The process of creating contemporary batik creations with local content in Probolinggo Regency uses a procedure for creating works of art consisting of three stages: exploration, design, and realization. The first stage is exploration, which includes searching, digging, and collecting data and references regarding sources of ideas about the Genggong flower in the Karangbong Village area. The second stage includes (1) design, namely exploring forms and techniques; (2) visualization of ideas, making the selected sketch a form of prototype model. The third stage includes (1) embodiment, developing/refining selected sketches for designs in the batik creation process. This creation process produces contemporary batik designs as a form of conservation effort in the Probolinggo Regency area.